Chemoenzymatic Synthesis of Original Stilbene Dimers Possessing Wnt Inhibition Activity in Triple-Negative Breast Cancer Cells Using the Enzymatic Secretome of Botrytis cinerea Pers. - Robin Huber (Frontiers in Chemistry, 2022)
The Wnt signaling pathway controls multiple events during embryonic development of multicellular animals and is carcinogenic when aberrantly activated in adults. Breast cancer and triple-negative breast cancer (TNBC) in particular depend upon Wnt pathway overactivation. Despite this importance, no Wnt pathway-targeting drugs are currently available, which necessitates novel approaches to search for therapeutically relevant compounds targeting this oncogenic pathway. Stilbene analogs represent an under-explored field of therapeutic natural products research. In the present work, a library of complex stilbene derivatives was obtained through biotransformation of a mixture of resveratrol and pterostilbene using the enzymatic secretome of Botrytis cinerea. To improve the chemodiversity, the reactions were performed using i-PrOH, n-BuOH, i-BuOH, EtOH, or MeOH as cosolvents. Using this strategy, a series of 73 unusual derivatives was generated distributed among 6 scaffolds; 55 derivatives represent novel compounds. The structure of each compound isolated was determined by nuclear magnetic resonance and high-resolution mass spectrometry. The inhibitory activity of the isolated compounds against the oncogenic Wnt pathway was comprehensively quantified and correlated with their capacity to inhibit the growth of the cancer cells, leading to insights into structure-activity relationships of the derivatives. Finally, we have dissected mechanistic details of the stilbene derivatives activity within the pathway.